A produção de sentidos sobre as queimadas na Amazônia a partir das reportagens do Fantástico: recepção, cidadania e meio ambiente - Jorge, Taynara Flávia Sanches (2024)
The environmental crisis, particularly the advance of deforestation and wildfires in Brazil, with a focus on the Amazon, has been widely covered in the press in recent years. Due to this environmental collapse occurring in Brazil and around the world, this research aims to analyze the production of meaning by employees of an industry that has sustainability as a corporate pillar, based on their reception of media coverage about the Amazon wildfires and environmental preservation. The study's objective is to analyze how the employees of Vasap Design perceive and reinterpret the topic based on content presented by the program Fantástico on Rede Globo. The theoretical framework of the work is based on Reception Studies and the concepts of Mediatization, Citizenship, and Environmental Journalism, with the main cited authors being J.B. Thompson, José Luiz Braga, Wilson Bueno, Jesús Martín-Barbero, Maria Immacolata Vassalo de Lopes, and Nilda Jacks. A multi-methodological study was chosen through reception analysis in a case study, using focus groups as the data collection technique. This method allows the researcher to combine in-depth interviews with participant observation, techniques widely used in qualitative research like this one. Thus, it was understood that although the environmental issue is a global and broad topic, it makes sense for this study to focus on a local context. For this reason, the research was directed toward a case study in the workplace, focusing on the daily experiences of employees and their lives in a company that positions itself as environmentally responsible. This choice allowed for observing how subjectivities, both individual and collective, are formed based on the reception of information by the media and work as a mediating factor. Therefore, the hypothesis underlying this study is that the professional environment acts as an important mediator in how individuals receive and process media messages. For the systematization and analysis of data, it was understood that the most suitable technique for this research is Content Analysis, as proposed by Laurence Bardin, which was carried out in two stages. The first stage involved categorizing and analyzing the environmental coverage of the program Fantástico from 2018 to 2021, so that, through this initial analysis, the reports discussed in the focus groups could be defined. Then, Content Analysis was used again to categorize and infer the reflections raised in the discussion groups. From these reflections, it was possible to identify that the environmental theme permeates the discussions among Vasap Design employees, especially in the workplace, which means that when they watch the presented reports, they already have some affinity with issues such as the Amazon wildfires and the environmental crisis. It was also observed that although the reports used as the research corpus presented relevant and complete information about the environmental collapse that Brazil is facing, the central focus was on the consequences of wildfires and deforestation. The causes and, especially, the solutions were subtly addressed, which contributed to the employees' understanding of the catastrophic scenario of the wildfires in Brazil, but did not enhance their perception of how society and each individual contribute to the problem and also to its mitigation. Thus, the research leads to the understanding of the media as an important tool for promoting citizenship, especially when combined with other forms of mediation that enable dialogue on environmental issues.